Strengthened seed regulations and certification system in Afghanistan - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2020)
Improving smallholder farmers’ access to high-quality seeds is among the key objectives of CGIAR. Achieving this goal requires a conducive policy and regulatory environment. Partnerships between public and private stakeholders for seed certification have proven successful in many countries. In Afghanistan, the engagement of CGIAR with the government resulted in a strengthened seed certification and seed market system through implementation of the public-private-producers partnership business model.